2019
DOI: 10.3389/fpsyt.2019.00093
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification and Intervention of Schizophrenia: Insight From Hypotheses of Glutamate Dysfunction and Oxidative Stress

Abstract: Schizophrenia is a severe mental disorder which leads to functional deterioration. Early detection and intervention are vital for better prognosis. However, the diagnosis of schizophrenia still depends on clinical observation to date. Without reliable biomarkers, schizophrenia is difficult to detect in its early phase. Further, there is no approved medication for prodromal schizophrenia because current antipsychotics fail to show satisfactory efficacy and safety. Therefore, to develop an effective early diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 124 publications
0
52
0
2
Order By: Relevance
“…In addition, current knowledge on treating schizophrenia with antioxidants is presented, along with information on how antioxidant levels in patients with schizophrenia may be regulated by nutritional, pharmacological, and lifestyle factors. Because schizophrenia is a progressive disorder from its onset in adolescence or early adulthood [ 10 , 26 , 27 , 28 ], the intake of natural antioxidants may help regulate its development [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, current knowledge on treating schizophrenia with antioxidants is presented, along with information on how antioxidant levels in patients with schizophrenia may be regulated by nutritional, pharmacological, and lifestyle factors. Because schizophrenia is a progressive disorder from its onset in adolescence or early adulthood [ 10 , 26 , 27 , 28 ], the intake of natural antioxidants may help regulate its development [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of the extensive literature studies is to identify potential biomarkers that play an important role in clinical practice supporting the diagnostic and therapeutic of SCZ [42]. These studies are important for all medical and mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Although these potential biomarkers are still in their infancy, it would be interesting to search for potential biomarkers through blood-based or brain imaging approaches. For instance, G72, functioning as a D-amino acid oxidase (DAAO) activator (DAOA), plays an important role in dysregulation of the glutamate system, and has been found to be a potential biomarker with excellent sensitivity and speci city [42]. Lin et al demonstrated that the plasma G72 protein levels were signi cantly increased in both medicated and drug-free patients with SCZ than in healthy controls [43] and the nding has been independently veri ed [44].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed increased glutamate/glutamine in children with a parent with a schizophrenia diagnosis (Tibbo et al, 2004) and a more recent report showed reduced glutamine in the occipital cortex in a combined sample of healthy relatives and patients with schizophrenia compared to healthy control subjects (thus indicating a role of cortical glutamine in disease liability) (Thakkar et al, 2017). The increased glutamatergic tone in MIA rats could also be a consequence of increased oxidative stress in the cortex (Lin and Lane, 2019). In support of this, (Vernon et al, 2015), reported decreased cortical levels of the antioxidant glutathione in rats exposed to poly I:C during gestation.…”
Section: Glutamate Glutamine and N-acetylaspartatementioning
confidence: 99%